PENDAMPINGAN MANAJEMEN KEUANGAN DAN TRANSAKSI PEMBAYARAN DIGITAL MELALUI QRIS DI DESA JATIBATUR KECAMATAN GEMOLONG KABUPATEN SRAGEN - Nurdyastuti, Tri; Suroto, Suroto; Mulyadi, Mulyadi; Fatonah, Siti (Sekolah Tinggi Ilmu Ekonomi AMA, 2026)
Jatibatur Village, Gemolong District, Sragen Regency, has significant economic potential, particularly through MSME activities in the trade, culinary, and service sectors. However, most transactions are still conducted in cash, which potentially poses security risks, limited financial record keeping, and is inefficient on a business scale. In this context, through this community service activity, the Jatibatur Village community is provided with outreach and assistance regarding simple financial record keeping as well as training on the use of the ORIS application. It is hoped that this activity will improve financial literacy, expand the use of digital transactions, and support the acceleration of the digitalization of the village economy as initiated by the government. The implemented strategies include Initial Problem Identification by conducting discussions and interviews with the community and MSMEs in Jatibatur Village to identify the main obstacles in financial management and the implementation of digital transactions through ORIS. Financial literacy outreach and counseling by providing education on the importance of simple financial record keeping, cash flow management, and the benefits of non-cash transactions. This strategy aims to increase public awareness of the importance of financial management for business sustainability. Technical training on the use of ORIS, individual and group mentoring, periodic monitoring and evaluation, and finally collaboration with the village government and financial partners. In general, the results of the activities show that the participatory mentoring strategy is effective in improving financial literacy and digital skills in the community.